Coupling coefficient observer based on Kalman filter for dynamic wireless charging systems - Nguyen Kien Trung; Nguyen Thi Diep (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
In the dynamic wireless charging system for electric vehicles, the transfer efficiency reaches the maximum value when the load impedance is equal to the optimal impedance value. However, the optimal impedance value depends on the coupling coefficient, which varies with the electric vehicle's position. Therefore, to track the optimal impedance as well as to improve the transfer efficiency, it is necessary to know the coupling coefficient. This paper proposes a coupling coefficient observer method based on the Kalman filter. Then, on the secondary side, an optimal impedance controller acts on the active rectifier to improve efficiency. The results show that the estimation method achieves high accuracy. The estimated error of the mutual inductance is less than 5% in both the case of impact measurement noise and change system parameters. System efficiency improved by 3.2% compared with the conventional estimation method.